Vowel Quality and Vowel Length in English as a Lingua Franca in Spain - Jurado-Bravo, María Ángeles (Miscelánea: A Journal of English and American Studies, 2018)
In today’s globalised world, the use of English as a Lingua Franca (ELF) is a reality. Given the fact that pronunciation deviations from the native-speaker norm are one of the main causes of communication breakdown (Jenkins 2000), it feels necessary to investigate which aspects of pronunciation constitute a communication hindrance if produced in a non native-like manner and which may allow some variation without loss of intelligibility. This paper aims at contributing to the existing literature related to vowel quality and intelligibility in ELF. Our hypothesis is that vowel length distinctions alone cannot ensure the intelligibility of English spoken by Spanish speakers, but that vowel quality does play a role in avoiding communication breakdown. A panel of listeners from different countries completed an intelligibility test in which they listened to several sentences and filled in a gap by choosing the word they thought had been uttered. Results show that vowel length seems to be a crucial vocalic feature in the avoidance of miscommunications, but that vowel quality is also necessary to maintain intelligibility, contrary to what the original Lingua Franca Core (LFC) originally suggested.